Land Collectivization and the Structural Transformation of Traditional Rural Families. (2nd July 2016) - Tianfu, Wang; Fei, Wang; Youcai, Tang; Youcai, Tang; ,
Abstract: We use oral history materials from elderly rural people aged over seventy to analyze the circumstances of rural family production and daily life prior to collectivization in the mid-1950s; during collectivization in the 1950s to the 1970s; and under the household contract responsibility system of the late 1970s. We find that the transition from the traditional to the nuclear family did not involve industrialization in the traditional Western sense. As an early state industrialization strategy after 1949, rural collectivization fundamentally changed the organizational pattern of traditional family production and daily life and of inter-generational relations and structures under the patriarchal system, launching the historical process of structural transition in the family. This explanation differs from the classic "theory of modernization" of family change.